Análisis de los canales de distribución para la asociación de criadero de ovinos “señor de maca”, de la parroquia Poalo del cantón Latacunga en el periodo 2014 - Tipán Rea, Sandra Verónica (2015)
The constant changes in the fashion and the increase of the competition make necessary that the Association “Señor de Maca” realizes an analysis of the channels of commercialization for its products are prepared. The aim was to realize the market research the objective of market commercialization conditions by means of the appropriate distribution channel and the design strategies of marketing. As justification has the interest to realize this investigation is due that in the community a reasonable population exists and therefore it is necessary to create sources work that guarantees its economic and productive stability inside the community “Maca Grande” of the parish Poalo….